Resposta do maracujazeiro-amarelo à salinidade da água sob diferentes formas de plantio1 - Cavalcante, Lourival F.; Dantas, Tony A. G.; Andrade, Raimundo; Sá, José R.; Macêdo, João P. S.; Gondim, Saulo C.; Cavalcante, Ítalo H. L. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2021)
In order to evaluate the effects of salinity water irrigation at levels of 0.5; 1.5 and 2.5 dS m-1 under different planting types on growth and production of yellow passion fruit plants, Passiflora edulis f. flavicarpa Deg., was carried out during the period of May 2001 to March 2002 an experiment in Remígio County Paraíba State, Brazil. The planting types were: a) conventional planting; b) planting in caves with covering of lateral sides with polyethylene film; c) planting in polyethylene bags with 60 cm of height and 40 cm of diameter. The plants presents the stem diameter and production more inhibited by planting types in relation to increment of salinity water irrigation. The planting type than more inhibited the growth and plants production and increased the soil salinity was in polyethylene bags. The soil water content and electrical conductivity values increased as function of the loss hydric reduction of the reduction soil in sequence: planting in polyethylene bags > planting in caves with polyethylene film in lateral sides > planting in traditional form.

Com a finalidade de avaliar os efeitos da salinidade da água de irrigação com valores de 0,5, 1,5 e 2,5 dS m-1 e diferentes formas de plantio, sobre o crescimento e a produção do maracujazeiro-amarelo (Passiflora edulis f. flavicarpa Deg.), desenvolveu-se este experimento, no período de maio de 2001 a março de 2002, no município de Remígio, Paraíba. As formas de plantio foram: a) convencional; b) em covas, com as faces laterais protegidas com filme de polietileno e c) em bolsas de polietileno, com 40 cm de diâmetro e 60 cm de altura. O diâmetro caulinar e a produção das plantas foram mais inibidos pelos sistemas de cultivo que pelo aumento de salinidade da água. O tipo de plantio que mais prejudicou as plantas e salinizou o solo foi em bolsas de polietileno. A umidade e a condutividade elétrica aumentaram em função da redução das perdas hídricas do solo, na ordem: cultivo em bolsas de polietileno > em covas com as faces protegidas lateralmente > no sistema de cultivo convencional.
Response of yellow passion fruit to salinity water irrigation under differents planting type
Keywords: Passiflora edulis; irrigation; saline water; planting system; Passiflora edulis; irrigação; água salina; sistema de cultivo